International financial sector reform : standard setting and infrastructure development - Arner, Douglas W.; Goo, S. H.; Zhou, Zhongfei; University of Hong Kong. (Boston, Mass. : Kluwer Law International, 2002)
In the wake of the Asian financial crisis that erupted in 1997, an intense scrutiny of the principles and standards of the world's financial system was inevitable. This book presents the insight and practical proposals of 25 experts relating to this matter.
At head of title: Asian Institute of International Financial Law, the University of Hong Kong.
Papers presented at a series of international conferences held in 199-2000 in collaboration with leading law faculties in the United States, United Kingdom, and other countries.
Published in cooperation with International Financial Law Unit, Centre for Commercial Law Studies, University of London and others.
Includes bibliographical references and index.
oif 21/07/14
Loan
Keywords: International finance; Banks and banking, International; Financial institutions, International